Gleak: The development of gas leakage detection system using IOT technology - Dahab, Kyle Andrey T.; Medina, Andrea Nicole E.; Siena, Mark Anthony U. 4 0 16; 5 (2023)
ABSTRACT: Gas leakage is the unintentional discharge of gaseous substances into any location where they should not be present. The potential for numerous accidents that result in property damage and physical injuries is due to the gas properties, such as toxicity, flammability, explosivity, etc. Liquefied petroleum gas can also be quite hard to detect as it can be obscured by stronger odors or smells that may come from food. It is also invisible to the naked eye. In this study, the researchers developed a system that detects liquefied petroleum gas leakage and immediately notifies nearby users that are affected through the use of an ESP32 microcontroller, MQ-6 gas sensor, and a passive buzzer module. The results show that the researchers have successfully achieved their objective of detecting the inadvertent outflow of liquefied petroleum gas and notifying affected users via buzzer and email application. The evaluation of the study using ISO 25010 shows that the system has excellent Functional Suitability and Usability with a mean of 4.84 and 4.72, respectively.
Undergraduate Thesis: (Bachelor of Science in Information Technology) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2